The Influence of Customer Experience, Personalized Marketing, and Brand Trust on Fashion Purchase Decisions on Shopee among Consumers in Medan City - Juliana Phannoto; Jennsen Jennsen; Justin Fernando; Januardin Januardin; Rintan Saragih (International Journal of Marketing & Human Resource Research, 2026)
The rapid development of e-commerce in Indonesia has significantly transformed consumer purchasing behavior, particularly in online fashion shopping via Shopee, one of the country's most dominant e-commerce platforms. This study aims to analyze the influence of customer experience, personalized marketing, and brand trust on fashion product purchase decisions on Shopee among consumers in Medan City. This research employed a quantitative approach with a cross-sectional design. A total of 300 respondents were selected using non-probability sampling, defined as active Shopee users who had purchased fashion products within the last six months. Data were collected through a Likert-scale questionnaire, and data analysis was conducted using multiple linear regression with SPSS version 25.The results indicate that customer experience, personalized marketing, and brand trust each have a positive and significant effect on purchase decisions. Brand trust emerged as the most dominant variable, with the highest regression coefficient, suggesting that trust in the platform and sellers plays a crucial role in reducing perceived risk and enhancing consumer confidence in purchasing decisions. Simultaneously, the three independent variables significantly influence purchase decisions, with an R-square value of 0.256, indicating that the model explains 25.6% of the variance in consumer purchase decisions. These findings emphasize the importance of enhancing user experience, implementing personalized marketing strategies, and strengthening brand trust to stimulate purchase decisions on e-commerce platforms. This study contributes both theoretically and practically to the development of digital marketing strategies, particularly in the fashion sector within the Shopee marketplace